Therapeutic Potential of Extracellular Vesicles for Demyelinating Diseases; Challenges and Opportunities - Osorio-Querejeta, Iñaki; Alberro, Ainhoa; Muñoz-Culla, Maider; Mäger, Imre; Otaegui, David (Frontiers in Molecular Neuroscience, 2018)
Multiple Sclerosis is a demyelinating disease of the central nervous system for which no remyelination therapy is available and alternative strategies are being tested. Extracellular vesicles (EVs) have emerged as players in physiological and pathological processes and are being proposed as therapeutic targets and mediators. More concretely, EVs have shown to be involved in myelination related processes such as axon-oligodendrocyte communication or oligodendrocyte precursor cell migration. In addition, EVs have been shown to carry genetic material and small compounds, and to be able to cross the Blood Brain Barrier. This scenario led scientist to test the ability of EVs as myelin regeneration promoters in demyelinating diseases. In this review we will address the use of EVs as remyelination promoters and the challenges and opportunities of this therapy will be discussed.